Implant choice impacts initial tibial component micromotion in total ankle replacement: A biomechanical analysis - Henry, Jensen; Hoffman, Jeffrey; de Almeida Tenório Villar, Ricardo Ummen; Lu, Kira; Steineman, Brett; Demetracopoulos, Constantine (Journal of the Foot & Ankle, 2026)
Introduction: Despite advances in technique and implant design, total ankle replacement remains at risk of early mechanical failure. Clinical data suggest that tibial components with more robust fixation, particularly stemmed designs, have lower rates of early aseptic loosening. One proposed explanation is improved load transfer and reduced micromotion at the bone-implant interface. This study compared tibial component micromotion between stemmed and low-profile peg fixation implants using a cadaveric robotic gait simulator. We hypothesized that stemmed implants would demonstrate less micromotion during stance. Methods: Five matched cadaveric pairs underwent computed tomography (CT) scans to create patient-specific instrumentation. Each specimen received either a low-profile peg or a stemmed tibial component in a randomized order. After implantation, gait was simulated with a validated robotic system that rotates a force plate beneath a fixed tibia. A digital image correlation system tracked surface markers to measure the relative motion between the bone and the implant. Post-simulation CT scans generated segmented geometries, and rigid-body transformations were used to calculate implant micromotion. Peak micromotion was defined as the maximum nodal displacement on the implant surface during stance. Paired t tests compared matched specimens. Results: Mean peak micromotion was significantly greater in low-profile implants than in stemmed implants, measuring 382 versus 240 micrometers. In every matched pair, the low-profile design demonstrated higher micromotion, with an average increase of 59 percent. Peak motion in low-profile implants occurred posteriorly, consistent with sagittal rocking. In contrast, micromotion in stemmed implants was more evenly distributed and directed superiorly into bone. Conclusion: Stemmed tibial components showed significantly less time-zero micromotion than low-profile peg designs. Excess posterior rocking in low-profile implants may contribute to early failure and subsidence.